Successful pregnancy outcome in a patient with Robertsonian translocation (13; 14) (Q10:Q10) with recurrent pregnancy loss - Singh, Kalpana; Bharti, Geetam; Prasad, Dipali; Ranjan, Rajeev (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Robertsonian translocations are unique type of whole-arm translocation that result from ‘centric fusion’ of the long arms of two acrocentric chromosomes with loss of the short arms, thus reducing the number of chromosomes by one. RT’s are present in 0.1% of the general population and 1% of the infertile population. Most frequent type of RT includes translocation rob (13; 14), whereas translocation rob (13; 15) and rob (14; 15) are rare. In the present report, RT in a female with spontaneous repeated abortions and infertility is reported. Cytogenetic analysis of a couple with repeated abortions revealed the presence of 45, XX, rob (13; 14) (q10; q10) chromosomal constitution in the female partner. The patient conceived after diagnostic laparoscopy followed by ovulation induction and intra uterine insemination and with proper antenatal care and support she delivered a healthy male baby with normal karyotype. The history of repeated abortions and infertility could be the outcome of unbalanced gametes (either monosomy or trisomy) resulting during the meiotic segregation of the balanced heterozygote female carrier. Cytogenetic analysis should be offered to all couples with unexplained recurrent abortions to evaluate the probable presence of any chromosomal aberrations.